UPAYA PENANGANAN TERHADAP ANAK KORBAN KEKERASAN SEKSUAL (Studi Kasus DP2KBP3A di Kabupaten Kuantan Singingi) - Marweni; M Zulherawan (Sisi Lain Realita, 2024)
This study discusses the efforts of DP2KBP3A Kuantan Dingingi Regency in dealing with cases of sexual violance against children. This study aims to determine how DP2KBP3A Kuantan Singingi Regency in handling cases of sexual abuse against children. The method used in this study is a qualitative descriptive approach by conducting interviews with 5 key informants and 3 informants in this study. The results of this study indicate that efforts to handle cases of sexual violance against children can run as they are. From receiving public complaints, going to the field, case management, temporary shelter, mediation, victim assistance and outreach to villages in Kuantan Singingi district. However, the implementation of the efforts of victims of child sexual violence in DP2KBP3A Kuantan Singingi Regency is still ineffective and there is a need for public awareness about acts of sexual violence against children.